2019
DOI: 10.1177/1044389419837069
|View full text |Cite
|
Sign up to set email alerts
|

Voices Should Be Heard: What Personal Stories of Homelessness Teach Us About Practice

Abstract: The Voices Should Be Heard community-based participatory research project provided a platform for individuals experiencing homelessness to share their life stories and experiences. Participants offered their reflections on the oppression of homelessness and how the service delivery system could be improved. This article synthesizes these reflections and offers recommendations for practice aimed at reducing the oppression of homelessness and promoting social change. Using a strengths-based perspective, we offer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…Similar findings emanated from a South African study by Alpaslan (2011), and by Grenier et al (2016c) in Canada, andSchneider et al (2019) in the USA. Malindi and Theron (2010) identified that street youth show hidden resilience to resile.…”
Section: Discussionsupporting
confidence: 88%
“…Similar findings emanated from a South African study by Alpaslan (2011), and by Grenier et al (2016c) in Canada, andSchneider et al (2019) in the USA. Malindi and Theron (2010) identified that street youth show hidden resilience to resile.…”
Section: Discussionsupporting
confidence: 88%
“…Researchers have indicated a disconnection between the services available to individuals’ experiencing homelessness, and the services that are actually required (Schneider et al, 2019 ). Alongside the material burdens of homelessness, issues of positive self-image, coping with social isolation, drug and alcohol misuse, violence, communicable diseases, and mental illness can affect homeless individuals (Barker et al, 2018 ; Schneider et al, 2019 ). However, service providers frequently focus on concrete needs, such as housing and income, and they may lack the training or capacity to attend to psychological needs.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have demonstrated that some of the most important factors in pulling oneself out of homelessness is positive self-esteem, a strong sense of self-worth, and a capacity for hope (Schneider et al, 2019 ). In a qualitative study conducted by Rea ( 2023 ), friendships with other people experiencing homelessness was discussed by half of the sample ( n = 20).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The need to synchronize available time with the pace of the respondents is well known in participatory research (cf. Schneider et al, 2019) and also experienced with the young adults with DLD. The respondents regularly showed their appreciation for TOSKoploper as a platform where they could finally take enough time in order to be understood or make use of alternative, creative means, such as Jamboard and drawing graphic stories with an illustrator, to bring their stumbling blocks of living with DLD in the limelight.…”
Section: Discussionmentioning
confidence: 98%